Pemasaran Holistik sebagai Strategi Tata Kelola Lembaga Pendidikan Islam dalam Meningkatkan Daya Saing - Indria Ningrum, Tiara; Panca Putera, Rachmat (Journal of Golden Generation Education, 2025)
Increasing competition among educational institutions requires Islamic schools and madrasahs to adopt strategies that go beyond promotional activities and focus on strengthening institutional governance and value creation. This article aims to conceptually examine holistic marketing as a governance-based strategy for enhancing the competitiveness of Islamic educational institutions. This study employs a qualitative approach using library research by critically reviewing scholarly books and journal articles related to holistic marketing, educational service marketing, and Islamic education management. The findings indicate that holistic marketing encompassing internal marketing, external marketing, relationship marketing, and performance marketing can foster sustainable competitive advantage for Islamic educational institutions. This approach ensures consistency between Islamic values, educational service quality, and public trust. Therefore, holistic marketing can be positioned as a strategic governance framework for Islamic schools and madrasahs in strengthening value-based competitiveness.